The Influence of Work Motivation on Employee Work Productivity In PT. Sentralsari Primasentosa (Cleo Sumedang Branch 2) - Amanda, Helles; Nuraeni, Fitria; Anggraeni, Vanny Maulidia; Zaharani, Salsa Alissya; Putri, Jihan Adienda; Asmarani, Diyah Ayu Putri (SINTESA, 2025)
This study aims to examine the effect of work motivation on employee productivity at PT Sentralsari Primasentosa (Cleo Sumedang 2 Branch), a registered distributor of Cleo bottled water. The research employs a quantitative approach using a survey technique with questionnaires, supported by qualitative data through in-depth interviews. Work motivation variables are measured based on Abraham Maslow's hierarchy of needs theory, while employee productivity indicators refer to the concept by Malayu S.P. Hasibuan.The questionnaire results from 20 respondents show that the majority of employees demonstrate a high level of work motivation, particularly in aspects such as adequate salary, team contribution, opportunities for self-development, and the ability to overcome work challenges. Meanwhile, interview findings indicate that the company actively implements motivational programs such as regular evaluations, a reward and punishment system, career promotions, and informal activities that strengthen employee relationships. These findings indicate that the company’s management strategies have effectively fulfilled various employee needs, which in turn contribute to increased productivity. The study supports the idea that comprehensive fulfillment of employee motivation significantly impacts employee behavior and performance, particularly in a distribution-based work environment.